Base-mediated intramolecular one-pot double-cyclization of epoxide-tethered 2-fluorobenzenesulfonamides: an avenue to 1, 4-benzoxazine-fused benzothiaoxazepine-1, 1-dioxides. Issue 2 (12th December 2019) - Das, Jonali; Borah, Biraj Jyoti; Das, Sajal Kumar
Abstract : A regio- and diastereoselective synthesis of pharmaceutically relevant 1, 4-benzoxazine-fused benzothiaoxazepine-1, 1-dioxides has been achieved under transition metal-free mild reaction conditions. Abstract : Herein, we describe the synthesis of hitherto unknown 1, 4-benzoxazine-fused benzothiaoxazepine-1, 1-dioxides by a NaH-promoted intramolecular one-pot double-cyclization of epoxide-tethered 2-fluorobenzene sulfonamides. Mechanistically, the reactions proceed via an intramolecular epoxide ring-opening followed by an intramolecular nucleophilic aromatic substitution. The high yields, mild conditions, complete regio- and diastereoselectivity, and a wide substrate scope render this protocol well suited for drug discovery efforts.